Brief Report: Use of the Consolidated Framework for Implementation Research (CFIR) to Characterize Health Care Workers' Perspectives on Financial Incentives to Increase Pediatric HIV Testing. (1st May 2020) - Atkins, Dana L.; Wagner, Anjuli D.; Zhang, Junyi; Njuguna, Irene N.; Neary, Jillian; Omondi, Vincent O.; Otieno, Verlinda A.; Ondeng'e, Kenneth; Wamalwa, Dalton C.; John-Stewart, Grace; Slyker, Jennifer A.; Beima-Sofie, Kristin
Abstract : Background: A prior randomized control trial showed financial incentives increase HIV testing rates for children of unknown HIV status. Translating evidence-based interventions such as these to scale requires an implementation science approach. Methods: A qualitative study evaluating health care providers' perceptions of barriers and facilitators of a previously completed financial incentives intervention for pediatric HIV testing was conducted at health care facilities in Kisumu, Kenya. Six focus group discussions with 52 providers explored determinants of acceptability, feasibility, and sustainability of financial incentive scale-up for pediatric HIV testing using the Consolidated Framework for Implementation Research to inform question guides and thematic analysis. Results: Providers found the use of financial incentive interventions for pediatric HIV testing to be highly acceptable. First, providers believed financial incentives had a relative advantage over existing strategies, because they overcame cost barriers and provided additional motivation to test; however, concerns about how financial incentives would be implemented influenced perceptions of feasibility and sustainability. Second, providers expressed concern that already overburdened staff and high costs of financial incentive programs would limit sustainability. Third, providers feared that financial incentives may negatively affect further care because of expectations of repeated financial support and program manipulation. Conclusions: Providers viewed financial incentives as an acceptable intervention to scale programmatically to increase uptake of pediatric testing. To ensure feasibility and sustainability of financial incentives in pediatric HIV testing programs, it will be important to clearly define target populations, manage expectations of continued financial support, and establish systems to track testing.